Il suono della rabbia - Una proposta di studio attraverso l’utilizzo della realtà virtuale per la rilevazione dei parametri vocali nell’esperienza della rabbia - Teresa Longobardi, Martina Messina, Yari Mirko Alfano, Alfonso Davide Di Sarno, Carmen Giannetti, Maria Guastaferro, Daniela Iennaco, Enrico Moretto, Nicole Nascivera, Tilde Annunziato (Phenomena Journal)
Traditional neuroscience has neglected the way in which the primary nature of emotions is generated by brain activity, due to the difficulty in measuring emotional phenomena by external observation. a set of new sciences, grouped under the name of “affective neuroscience”, is working to clarify the ways in which the mammalian brain generates affective evaluations of the events that occur in the form of nonverbal emotional states, and how the affects primitive emotions emerge from neuronal circuits located under the neocortex. In the past, emotions were considered by neuroscience studies as transient and reactive states, which interrupted the mental flow between a stimulus and a response. contemporary neurosciences, on the contrary, believe that they refer to involving active, perceptive, monitoring processes and in continuous adaptive and emotional development is considered by a set of organized components. this article discusses the scientific basis of emotions, the relationship between cognitive neuroscience and affective neuroscience, the effects of neuroscientific studies of emotions on psychopathology and the psychotherapeutic treatment of emotional dysfunction in psychiatric syndromes. a study hypothesis will be introduced in order to recognize the vocal parameters characteristic of the experience of anger with the help of Virtual reality.